(untitled) (Journal of Tourism & Development, 2022)
The preservation of heritage is of paramount importance for the tourism system, the use of social media and the role they play in the choice of visitors to tourist spaces has been the focus of many tourism researches. This study performs a netnography through a Facebook group to analyze the role that social media plays in the perception of security in tourist spaces and in the creation of the feeling of preservation of its cultural heritage in Tinguá neighborhood in the city of Nova Iguaçu - RJ. Based on the results obtained, this research found that social media are important for the promotion of tourism and influence the perception of security and the feeling of conservation of the cultural heritage of tourist spaces. Despite being a survey with limited geography and database, this article contributes to academia and tourism, in addition to identifying the tourist potential of the Tinguá region and provides suggestions for future research.